Analisa Optimalisasi Transisi Pelaporan SPT Tahunan Melalui Sistem Coretax untuk Ketepatan Pembayaran Wajib Pajak di KPP Pratama Sidoarjo Utara - Ariesta Maherani Laksono; Muhafidhah Novie; Chairil Anwar (CV. ALIM'SPUBLISHING, 2026)
Digital transformation in the tax sector is a strategy of the Direktorat Jendral Pajak (DJP) to improve the quality of service and taxpayer compliance. One form of this transformation is the implementation of the Coretax system as an integrated tax administration system that replaces the DJP Online system. This system change poses adaptation challenges for taxpayers, particularly in reporting Annual Tax Returns, which has the potential to affect the accuracy of tax payments. This study aims to analyze the optimization of the transition of Annual Tax Return reporting through the Coretax system on the accuracy of individual taxpayer payments at the North Sidoarjo Tax Office (KPP Pratama). The research method used is descriptive qualitative with data collection techniques such as observation of the Annual Tax Return reporting assistance process, documentation, and interviews with three taxpayers. The results show that the Coretax system is able to improve the accuracy of tax filing through data integration and automatic validation, thereby encouraging the accuracy of the amount and timeliness of tax payments. However, technical system constraints and limitations in taxpayer digital literacy were still encountered during the transition period. Assistance from tax officers and tax volunteers proved to be instrumental in helping taxpayers adapt to the Coretax system. This study concludes that optimizing the transition of the Coretax system requires a combination of system improvements and strengthening taxpayer education to achieve sustainable accuracy of tax payments.